Comunicación y participación de los estudiantes de segundo año de la Escuela Profesional de Educación Primaria de la Universidad Nacional de Trujillo, 2021 - Leiva Reyes, Luz Fiorella (2022)
The present investigation was carried out with the purpose of analyzing the influence of communication and the participation of second-year students of the Professional School of Primary Education of the National University of Trujillo. The population was 25 students whose ages ranged between 17 and 24 years old. During the development of the present investigation, three methods were applied: the inductivedeductive, the analytical-synthetic and the statistical; Research techniques such as the interview and the survey were also used, and instruments such as the interview guide, interview record and the questionnaire, which allowed obtaining quantitative and qualitative data allowing the understanding of the indicators and their variables. The results of the investigation were that communication directly influences participation, because students have developed their social skills, 92% practice the assertive style in their classes, 80% of them practice active listening with their teachers, 100% of them practice empathy with their peers and interpersonal relationships, showing that more than half of the students are interested in making friends to carry out their work with 92%, Initiative to start conversations 60% and confidence to express ideas 64%, all of the above mentioned are put into practice based on their sense of belonging since 100% of students are proud to be part of their professional school and 96% feel integrated, this increases participation .